Capital Buffer, Credit Risk and Liquidity Behaviour: Evidence for GCC Banks. Issue 4 (December 2016) - Ghosh, Saibal
Abstract We utilize data on Gulf Cooperation Council (GCC) banks for the period 1996–2012 to test the interrelationships among credit risk, capital and liquidity. The results indicate that banks simultaneously coordinate adjustments in capital, liquidity and risk. We show that during the pre-crisis period, adjustments in bank capital inversely affected risk andvice versa, an effect that turned positive in the post-crisis regime. In addition, we also find a significant and bidirectional relationship between bank risk and liquidity. We also establish that banks increase their liquidity when their capital buffers decline, and this effect is in evidence primarily during the post-crisis period. Finally, we also show that banks that hoarded liquidity exhibited lower loan growth, an effect that was multiplied during the crisis. Our results highlight the importance of incorporating liquidity ratios, in addition to capital requirements, as part of banking regulations.